Gambaran Karakteristik dan Manajemen Perawatan Diri Lansia Hipertensi - Orizani, Chindy Maria; Ngange, Florentina Natasia; Noi, Bernadethe Putrisia Oli; Doa, Maria Yunita; Wae, Anastasia Riani; Dhema, Grace Oktoriani Ito; Putri, Maretha Amalia; Putri, Nadzala Ananda; Zulfiyyah, Umi Shohifatuz; Adelia, Mauren; Prasetyo, Rayhan; Adhitya, Dhimas (Bagian Penelitian & Pengabdian Masyarakat STIKES Adi Husada, 2025)
Background: Hypertension is a common condition in older adults that requires effective self-care management. This management includes behavioral skills for self-management of the disease, which is essential for controlling hypertension. However, levels of self-care management in older adults tend to be low, and they often experience difficulties that can worsen their health condition. Many older adults perceive poor self-care management as normal, even though it can increase the risk of complications. Aims: to describe the characteristics of the elderly and self-care management in the elderly with hypertension Methods: This study was a descriptive design. The sample consisted of 100 elderly people with hypertension selected using quota sampling. The Self-Management Behavior Ability of patients with hypertension questionnaire was used. Results: The results showed that the majority of elderly people were aged 56-65 years (84 people). The majority of elderly women (86 people). Most respondents were unemployed/retired (69%). The highest level of education was higher education graduates (29 respondents). The duration of hypertension for the majority of elderly people (66 people) was 1-5 years. In addition, the majority of respondents (68 people) had poor (negative) self-care management. Conclusion: Optimal self-care management needs to be implemented to improve the elderly's ability to manage hypertension and maintain quality of life.